Pelatihan Pembuatan Jamu Instan Pada Masyarakat Di Desa Kemanisan Kecamatan Curug Serang Sebagai Upaya Peningkatan Kemandirian Ekonomi Keluarga - Yusransyah Yusransyah; Sofi Nurmay Stiani; Fathiyati Fathiyati; Sandy Nurlaela Rachman; Leni Halimatusyadiah; Endah Endah; Renditya Ismiyati; Andri Harpan; Meila Pertiwi (Jurnal Abdi Masyarakat Kita, 2023)
Traditional medicines are ingredients in the form of plant ingredients, animal ingredients, mineral ingredients, galenic preparations, or mixtures of these materials which have been used for generations for treatment and can be applied in accordance with the norms in force in society, while herbal medicine is a Traditional Medicine made in Indonesia. The purpose of this research is to increase understanding of the importance of increasing understanding regarding the processing of instant herbal medicine and raising awareness of the importance of improving skills in the form of training on making good and correct instant herbal medicine in Kemanisan village. The community service method used in this research is in the form of community relations through counseling and health training. The results showed that the knowledge level of the respondents before the training, namely 41,7 %, was in the sufficient category. The respondents' knowledge level after the training was 50% in the good category. Based on the study results, it can be concluded that the respondents' knowledge level before and after counseling and training increased their knowledge. Community service activities through counseling methods can increase respondents' knowledge regarding managing medicinal plants into an instant herbal products with economic value.